Implementation of Google Maps Geo Location Algorithm at Sate Padang Ajo Ramon Restaurant based on Android - Gusniarti; Fauziah; Winarsih (Institute of Computer Science (IOCS), 2020)
Andorid-based food ordering application is an application that can be used by people to order food online. Where customers can order food only by using a smartphone without visiting the restaurant in person. In general, when customers want to order food, they must visit a restaurant in person, choose a food menu and place an order. This is less efficient and effective because it requires costs and a long time, including waiting in line, being blocked by the weather on the way and stuck in traffic. Based on these problems, an android-based food ordering application is needed that can help customers order food quickly, view restaurant lists and food menus. Through this application, it can also help the seller or owner of each restaurant to simplify the management of food sales from the restaurant.